Understanding of Extremism in Education in Indonesia Perspective of Al-Mishbah Interpretation - David Rifai; M. Agus Mushodiq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Islamic Religious Education subjects taught to students at every level must be treated differently in terms of mindset. If a person is born and develops a thought process from the concrete to the abstract or from the simple to the complex, Islamic Religious Education must also develop following the mindset of the learner. Islamic Religious Education at the SD level in formal material can be the same as at the MI level. However, the ability of students to analyze, find values, and develop their mindset makes Islamic Religious Education subjects feel different. The purpose of this research is to find out the dialectical approach that is carried out by Hagel and how it is implemented when it is related to Madrasah Ibtidaiyah education. The type of research used in this study is a literature study with a qualitative descriptive approach. The result of this study is that the dialectical approach is very well used in learning at Madrasah Ibtidaiyah. This is done to train students' mindsets and make students better understand an Islamic Religious Education material.